Better support for children with additional health and developmental needs in school settings: Perspectives of education experts. (24th March 2020) - Garvey, William; O'Connor, Meredith; Quach, Jon; Goldfeld, Sharon
Abstract: Aim: Many children start school with additional health and developmental needs (AHDN), yet how best to support these children for optimal outcomes in the school setting is a complex challenge. This study aims to determine the views of education experts on what differentiates the most effective primary schools. Methods: Qualitative interviews were conducted with nine senior leaders across the education system responsible for managing or improving practice across a range of schools or school regions in Victoria. Using a positive deviance approach, which investigates strategies already implemented in organizations achieving desired outcomes, the semi‐structured interviews aimed to elicit instances of perceived good practice that already exists within the school system. Interviews were analysed using inductive content analysis. Results: All education experts reported high variability across schools and suggested a number of factors differentiating those that were most effective at supporting children with AHDN. They included the presence of strong teacher support by the school leadership team; explicit and documented processes to guide the practice of teachers and ensure consistency at a whole school level; inclusive relationships and environments; participation and knowledge sharing between medical, allied health and other stakeholders in the care team; and an evidenced‐based approach to allocating resources to programmes and strategies. Conclusion: This exploration of instances of good practice can generate novel insights into a complex problem. Current findings suggest a number of potential opportunities for enhancing practice that can be tested in future research. Improving outcomes for this vulnerable and significant group of children will require collaboration across health and education.